(untitled) (Coordinates of Public Administration, 2026)
The article examines the peculiarities of state regulation of information security under conditions of intensive digitalization of society and the growing scale of information threats accompanying the processes of digital transformation in public administration and social relations. The essence of information security as an important component of the national security system is revealed, and its role within the public administration system is defined in the context of ensuring social stability, protecting national interests, maintaining state information sovereignty, and minimizing the risks of destructive information influence. It has been established that contemporary digitalization processes, alongside expanding opportunities for the use of information and communication technologies, generate new challenges related to cyber threats, information manipulation, the dissemination of disinformation, interference in the functioning of state information systems, and violations of personal data security. Particular attention is devoted to the analysis of legal and institutional aspects of the formation and implementation of state policy in the field of information space protection. It has been determined that the modern system of state regulation of information security requires comprehensive legal and regulatory support capable of responding promptly to dynamic changes in the digital environment and adapting to emerging challenges and risks. The current state of legal and regulatory support for information security has been analyzed, and the main legislative acts and strategic documents governing activities in the fields of information and cybersecurity have been characterized. Furthermore, key directions for their improvement have been identified in the context of technological development and Ukraine’s integration into the European legal framework. It is substantiated that effective state regulation of information security is possible only through the integrated combination of legal norms, institutional mechanisms, and modern technological tools. It has been demonstrated that ensuring the resilience of the state information environment requires not only the modernization of the legislative framework but also strengthening the institutional capacity of public administration bodies, developing human resources, enhancing digital competencies, and establishing an effective system of strategic information security management. It is concluded that there is a need for further improvement of legal regulation, strengthening the institutional capacity of public administration bodies, and developing a sustainable system for protecting the state information space in the context of global digital transformations and the increasing scale of contemporary information challenges.